2007
DOI: 10.1177/030802260707000505
|View full text |Cite
|
Sign up to set email alerts
|

Art and Recovery in Mental Health: A Qualitative Investigation

Abstract: Arts programmes are provided as part of the psychosocial rehabilitation for consumers with a mental illness. Consumers have reported that involvement in the arts has facilitated their recovery. This qualitative study was conducted to explore the ways in which involvement in an Australian community arts programme contributed to the recovery process. It also aimed to gain an understanding of intrinsic recovery, which focuses on personal satisfaction and meaning. Eight consumers with a mental illness who were mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 15 publications
(29 reference statements)
2
83
0
7
Order By: Relevance
“…Griffiths highlighted the value in restoring the balance between work and leisure via creative activity but with many of the clients in our study being institutionalised on a long-term basis, value was derived from providing relaxing, engaging activities as alternatives to passive observation of a television screen, for instance. Lloyd et al (2007) discovered that clients were able to regulate their extent of expressed emotion through art, and could subsequently apply this sense of control to other aspects of their lives. Likewise, our study found decreased negative emotion as a result of object handling.…”
Section: Discussionmentioning
confidence: 99%
“…Griffiths highlighted the value in restoring the balance between work and leisure via creative activity but with many of the clients in our study being institutionalised on a long-term basis, value was derived from providing relaxing, engaging activities as alternatives to passive observation of a television screen, for instance. Lloyd et al (2007) discovered that clients were able to regulate their extent of expressed emotion through art, and could subsequently apply this sense of control to other aspects of their lives. Likewise, our study found decreased negative emotion as a result of object handling.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has been more broadly concerned with a range of creative activities including: painting, drawing, collage, card making, textiles, needlecraft, pottery and woodwork (Griffith, 2008;Lloyd, Wong, & Petchkovsky, 2007;Schmid, 2004). Griffith (2008) suggested that creative activities facilitate occupational gains, which can be grouped into manual skills, specific to the activity (sewing, drawing, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For many people art is also a preferred way of expressing thoughts and emotions (Perruzza & Kinsella, 2010). Art can enable people to regulate and control what and how much they choose to 5 communicate, resulting in a sense of empowerment and independence (Lloyd et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations